Evaluating the use of loop-mediated isothermal amplification (LAMP) method for detection of Mycobacterium tuberculosis in Indonesian clinical isolates (Medical Journal of Indonesia, 2012)
Background: Loop-mediated isothermal amplification (LAMP) is a method already claimed as a simple technique to amplify DNA/ RNA using four to six primers as "a set" from conserved sequence of target gene. In this study we optimize the use of LAMP for detection of Mycobacterium tuberculosis in clinical isolates from Indonesia. Methods: Procedures to perform LAMP were optimized, then the method was applied to 122 archieved samples of DNA's Mtb from clinical TB patients with Acid Fast Bacilli (AFB) smears positive. The samples were obtained in 2008 from 13 provinces in Indonesia for genotyping study, which then become collections of Center for Biomedical and Basic Technology of Health (CBBTH), NIHRD Indonesia. The optimization tests include sensitivity and specificity tests of several sets primers, which were evaluated using 10-fold serially diluted DNA of Mtb H37Rv and 12 species of Mycobacteria. Three equipments consisted of LAMP turbidimeter, heating block and water bath were compared for its ability in DNA amplification. Detection of M. tuberculosis from clinical isolates used set primers specific for gyrB gene, amplicon was detected with UV fluorescence system. Results: The results showed that the highest sensitivity was obtained using the set primers specific for 16S rRNA and gyrB which could detect 10.0 fg to 1.0 pg genomic DNA of Mtb H37Rv. The set primers specific for gyrB gene was the most specific primers. Application of LAMP using gyrB set primers on Indonesian clinical isolates showed 94.2% (114/121) positivity rate. Conclusion: LAMP method is potentially used in TB diagnosis in Indonesia. (Med J Indones. 2012;21:188-95)